Question:

If \( x^y = e^{x - y} \), prove that \( \frac{dy}{dx} = \frac{\log x}{(1 + \log x)^2} \):

Show Hint

For functions involving both \( x \) and \( y \), logarithmic differentiation often simplifies the process.
Hide Solution
collegedunia
Verified By Collegedunia

Solution and Explanation

Step 1: Take logarithms of both sides
The given equation is: \[ x^y = e^{x - y}. \] Taking the natural logarithm on both sides, we get: \[ \log(x^y) = \log(e^{x - y}). \] Step 2: Simplify using logarithmic properties
Using the properties of logarithms: \[ y \log x = x - y. \] Rearranging the terms to express \( y \): \[ y (1 + \log x) = x. \] Thus, we have: \[ y = \frac{x}{1 + \log x}. \] Step 3: Differentiate \( y \) with respect to \( x \)
Differentiate both sides of \( y = \frac{x}{1 + \log x} \) with respect to \( x \) using the quotient rule: \[ \frac{dy}{dx} = \frac{(1 + \log x) \cdot 1 - x \cdot \frac{1}{x}}{(1 + \log x)^2}. \] Step 4: Simplify the derivative
Simplify the numerator: \[ \frac{dy}{dx} = \frac{(1 + \log x) - 1}{(1 + \log x)^2}. \] This reduces to: \[ \frac{dy}{dx} = \frac{\log x}{(1 + \log x)^2}. \] Conclusion: 
The derivative is proved to be: \[ \frac{dy}{dx} = \frac{\log x}{(1 + \log x)^2}. \] 
 

Was this answer helpful?
0
0

Questions Asked in CBSE CLASS XII exam

View More Questions